Ultra-sonografia em surubins (Pseudoplatystoma caruscans): avaliação de parâmetros reprodutivos e características de carcaça - Daniel Vieira Crepaldi (2008)
Fish consumption is increasing in the last four decades, not only in demand but also for because of the changes in human feed consumption, that comes, each time more, searching products with adjusted nutricional profile. Aquaculture and fishing, in recent years, had reached great productivity, supplying the world-wide market with about 140 million tons of fish. Of this total, aquaculture is already responsible for approximately 43%. The Brazilian aquaculture grows fast, benefited for all the natural characteristics of the country. The most important fishproduced in Brazil are; tilápias, carps, trouts and other natives species. The chosen species to compose this study, Pseudoplatystoma coruscans, is a freshwater fish with a high commercial value. Is considered noble because of it´s low fat rate and absence of fishbone, however, few studies exists about its zootecnics characteristics as quality of carcass yield. Few fish farmers produce surubin´s fry. Reproduction in captivity has a low efficiency due the problems in the identification of the ideal moment to beginning the spawning induction protocol. The aim of this work was evaluate the parameters of gonadal development of surubim, through ultrasound and the carcass yield of this species in different weight class. In the first stage, parameters for the evaluation of different gonadal maturation status was created during all the reproductive period, through the ultrasound, aiming the improvements in the detection of the ideal time to initiate the induced reproduction protocols. One hundred seventy-six surubins (P. coruscans)weighting between 2 and 46.2 kg had been evaluated. The fish were captured in the medium San Francisco river between 2004 and 2006. The accuracy identification of the final maturation status was 100%, and 94.6 % in the fish in reproductive rest. The gonad identification in immature or in reproductive rest status was difficult, as such for the characteristics of the same ones how much for the field research conditions. It was not possible to sex fish when those were young or in reproductive rest, however, in advanced phases of maturation it is possible to identify the females and to define the males by deduction. The possibility of making gonad evaluations in real time allows, with higher efficiency, the detection of the corrected moment to initiate reproduction induction protocols. In the second stage, was evaluated the carcass yield of Surubim in different weight class and the correlations between the biometric measures andthe height, width and area of the epi-axial muscle in ultrasound images. The animals were divided in 4 groups in accordance with their total weight. All groups were subjected to variance analysis student-Newman-Kells test (SNK) with 5% of probability for comparison of the means. All the correlations were statistically different between the analyzed groups, with the exception of the carcass yield (74,38%). Equations of regression were proposed, the best R² (R² = 0,87)was reached in equation in the group number 4 that related the total weight (PT) with the total length (CT). The correlations between the ultrasound measures, in the chosen point, and the biometric measures were low or with no significance. The excellent point to make ultrasound images for the lower weight class cannot be applied to specimens of greater size. There is a visible difference in the patterns of corporal growth of this species during its life cycle.